The role of the UN Security Council in combating piracy on the high seas - Muayed Abdulateef, Prof. Dr. Samer (Basra studies journal, 2023)
Maritime piracy is one of the most prominent threats to the safety of maritime transport, which is reflected successively on the international trade movement and, consequently, on peace and security in the regions that suffer from this problem, in addition to its other security problems that caused the emergence of this type of maritime crime. In view of the growing acts of maritime piracy and the development of its means and its extension even to the high seas areas in a manner that exceeds the ability of individual states to confront it in view of the wide field of its operations, it was necessary for the international community to move represented by the major countries concerned with this threat and with them the international and regional organizations led by the United Nations to confront the security threats that have become It is represented by the acts of maritime piracy, especially in the open seas, by taking an escalating series of important decisions and procedures that did not adhere to the scope of what was stated in the international agreements concerned with regulating these cases, but rather derived from the authorities provided for it by Chapter VII of the Charter of the United Nations, by deploying international forces in the areas that are active piracy, although there are many obstacles to these international endeavors. The study derives its importance from the need to demonstrate the seriousness of the threats posed by maritime piracy to the security and safety of maritime transport and the risks it causes from an economic point of view, as well as its effects on the security of coastal states, either because of these criminal operations or due to the intervention of the international community in their internal affairs to enable them From restoring the imposition of security, on the other hand, this research seeks to show the role of the international community and its active organization the United Nations and its most important organs (the Security Council) in finding appropriate solutions to eliminate or reduce the risk of maritime piracy to the maximum extent possible.